2018
DOI: 10.15766/mep_2374-8265.10727
|View full text |Cite
|
Sign up to set email alerts
|

How to Find an Academic Position After Residency: Who, What, When, Where, Why, and How

Abstract: IntroductionTransitioning from trainee to practicing physician is a process that is not frequently discussed during postgraduate training, but such a discussion is necessary if the number of academic physicians is to increase and physicians from underrepresented communities are to gain insight about the varied opportunities to join academe. This workshop combines a case-based format in its didactic portion with a step-by-step guide and time line to introduce the process for securing an academic position postre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Conferences provide diversified learning opportunities that might not be possible in the setting of conventional didactic education. Residents have previously relied on conferences to learn about practice at other institutions, network with mentors and help with job search ( 21 , 22 ). While 14 major national and international Radiology meetings have already been canceled or postponed between March and June 2020, the Radiological Society of North America (RSNA) has announced plans to hold the 2020 Annual Meeting – originally planned for November 29 – December 5, 2020 in Chicago - as a virtual event.…”
Section: Discussionmentioning
confidence: 99%
“…Conferences provide diversified learning opportunities that might not be possible in the setting of conventional didactic education. Residents have previously relied on conferences to learn about practice at other institutions, network with mentors and help with job search ( 21 , 22 ). While 14 major national and international Radiology meetings have already been canceled or postponed between March and June 2020, the Radiological Society of North America (RSNA) has announced plans to hold the 2020 Annual Meeting – originally planned for November 29 – December 5, 2020 in Chicago - as a virtual event.…”
Section: Discussionmentioning
confidence: 99%
“…The job search timeline and the challenges identified by NPM fellows are shared by many medical specialties [ 2 , 3 , 21 , 32 – 34 ]. A study of critical care medicine fellows showed that less than half of trainees receive formal guidance from mentors or their training programs on the job search [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been increasing reports of strategies to address the need for centralized resources and courses to prepare trainees for the job search. Several online resources, personal reflections, and descriptive papers now exist to guide trainees and program directors (PDs) [ 3 – 12 ]. Some have published curricula [ 13 16 ] or career panels [ 17 , 18 ] implemented at single institutions concerning individual components of the job search.…”
Section: Introductionmentioning
confidence: 99%
“…Internal medicine residents reported that starting more than 1 year in advance was among the best advice they received. 2 2. Define career goals and priorities.…”
Section: What Is Knownmentioning
confidence: 99%